Performance of Subsurface Drip Irrigation System with Line Source of Water Application in Okra Field - Singh, D K; Rajput, TBS; Singh, D K; Sikarwar, H S; Sahoo, R N; Ahmad, T (Journal of Agricultural Engineering, 2006)
Subsurface drip irrigation (SDI) is application of water below soil surface through the emitters, with discharge rates generally in the same range as surface drip irrigation. Performance of SDI with respect to uniformity of water and chemical application in a crop is an essential component for efficient management of SDI. A study was conducted to evaluate performance of SDI used for irrigating okra crop during 2003 and 2004. The parameters evaluated were pressure -discharge relationship of emitters, and uniformity of water application including discharge variation, coefficient of variation, uniformity coefficient, statistical uniformity, and distribution uniformity. The emitter discharge exponent was found to be 0.56 for inbuilt labyrinth type emitters used in SDI. The maximum values of standard deviation, variation and coefficient of variation of emitter flow rates were found to be 0.057, 0.08 and 0.025, respectively. Analysis revealed that statistical uniformity, distribution uniformity and uniformity coefficient were more than 90% during two years of study. Based on these parameters, performance of SDI was found excellent during study period.